(untitled) (Economic studies journal, 2025)
This study aims to analyze the relationship between free cash flows, agency costs, and the creditworthiness of the Libyan Iron and Steel Company during the period from (1996) to (2022). Based on the Agency Theory and the Pecking Order Theory, the effect of both free cash flow and agency costs on the company’s creditworthiness was tested. The results indicate that there is a positive and statistically significant effect of both free cash flows and agency costs on creditworthiness. The positive relationship between cash flow and creditworthiness is consistent with the Pecking Order Theory, which confirms that the company’s cash surplus reduces its reliance on debt. The positive relationship between agency costs and creditworthiness was interpreted as administrative spending in the context of the company was likely necessary to achieve growth, which enhanced its financial position and the trust of lenders. Thus, the study confirms the importance of these financial indicators in evaluating performance in a volatile environment. Additionally, the descriptive analysis revealed a large fluctuation in free cash flows and agency costs, indicating that the company faced changing economic and political conditions.